NCMP-17. BEWARE: ALL POSTERIOR FOSSA MASSES IN CHILDREN ARE NOT BRAIN TUMORS. (12th November 2021) - Issai Vanan, Magimairajan; Li, Jie; Almiski, Muhamad; Bunge, Martin; Serletis, Demitre; Israels, Sara
Abstract: INTRODUCTION: Isolated Myeloid sarcoma (MS) of the central nervous system (CNS-MS) is a very rare presentation of Acute Myeloid Leukemia (AML). A 10-year-old boy with a two-week history of intermittent headaches was referred to the emergency department (ED) by an optometrist for evaluation of bilateral papilledema. Physical examination in the ED confirmed the presence of papilledema with no other abnormal neurologic findings. Emergent MRI of the brain showed an avidly homogeneously enhancing extra-axial dural based mass in the right posterior fossa measuring 4.8 cm (AP) x 3.2 cm (CC) x 4.6cm (T), with significant mass effect and peri-tumoral vasogenic edema. Neuro-surgery consultation was obtained and complete blood count (CBC) was normal except for the presence of 13% blasts with occasional Auer rods seen on the peripheral blood smear. Bone marrow aspirate demonstrated 56% myeloblasts; A diagnosis of AML with CNS-MS (CNS-3c) was made and the initial lumbar puncture (LP) was deferred due to the risk of CNS herniation. Induction chemotherapy was initiated as per protocol. A CT scan done two weeks later showed complete resolution of the intracranial mass. DISCUSSION: The incidental finding of papilledema, with imaging to investigate the intracranial pathology revealed a large posterior fossa mass in our patient. However, the atypical features of the mass (dural based extra-axial location; extensive infiltration into adjacent structures) and the finding of blasts with Auer rods in peripheral blood helped us to diagnose CNS-MS, and avoided an extensive neurosurgical procedure and a delay in definitive therapy. Our patient had a normal CBC and the review of the peripheral blood film by an experienced Hematologist was very crucial in making a clinical diagnosis of MS. CONCLUSION: Myeloid sarcomas should be considered in the differential diagnosis of an intracranial mass, particularly when accompanied by abnormal findings in the CBC.